1997
DOI: 10.1139/f97-047
|View full text |Cite
|
Sign up to set email alerts
|

Cycles of abundance among Fraser River sockeye salmon (Oncorhynchus nerka)

Abstract: In some but not all populations of sockeye salmon (Oncorhynchus nerka) that mature mainly at age 4, there has been a persistently "dominant" line, a "subdominant" line about 10-25% as large, and two weak lines having less than 1% as many fish as the dominant one. Suggested causes of this phenomenon that have been shown to be wrong or inadequate are the presence of a few sockeye of ages 3 and 5 in the spawning stocks and a somewhat larger rate of harvest of the nondominant lines. The only plausible type of expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 24 publications
1
57
0
Order By: Relevance
“…Provided that the local habitat remains suitable, all but a few members of any population can be wiped out and the population will recover its former abundance in a few generations. A dramatic example of this capacity was shown by Fraser River sockeye salmon (O. nerka) stocks that recovered after nearly being wiped out by overfishing and a rock slide at Hell's Gate in 1913 that blocked most fish from migrating upstream (Ricker 1987). Schtickzelle and Quinn (2007) used Bristol Bay sockeye as an illustrative case to argue that groups of Pacific salmon populations are organized as a metapopulation.…”
Section: High Reproductive Capacitymentioning
confidence: 99%
“…Provided that the local habitat remains suitable, all but a few members of any population can be wiped out and the population will recover its former abundance in a few generations. A dramatic example of this capacity was shown by Fraser River sockeye salmon (O. nerka) stocks that recovered after nearly being wiped out by overfishing and a rock slide at Hell's Gate in 1913 that blocked most fish from migrating upstream (Ricker 1987). Schtickzelle and Quinn (2007) used Bristol Bay sockeye as an illustrative case to argue that groups of Pacific salmon populations are organized as a metapopulation.…”
Section: High Reproductive Capacitymentioning
confidence: 99%
“…Cyclic dominance refers to the disparity in population size of different "lines" of sockeye giving rise to 4-year cycles in a number of populations. Ricker (1997) reviewed potential underlying ecological and fishery-related mechanisms giving rise to this fascinating periodic pattern (Figure 10; upper panel). Myers et al (1998) showed that the interplay of harvesting and stochastic forcing can recreate basic patterns of this type for certain ranges of the parameter space and exploitation levels in a Ricker model (see Box 5).…”
Section: Fishing and Dynamical Responsementioning
confidence: 99%
“…21 Gisdaywa illustrated this point further by explaining that where the Wet'suwet'en and Babine territories met it was often the same clan that controlled the territory on either side of the line. 22 He noted that Smogelgem had nephews from Babine that would often come into Wet'suwet'en territory and trap with their uncle on his territory. 23 This combination of clearly delineated territorial boundaries and exceptionally intricate familial ties was part of a larger push-pull between the Babine and Wet'suwet'en.…”
Section: A Complex Culturementioning
confidence: 99%
“…This, according to Goldman, began about "150 years ago, a century before direct contact with the Whites" and allowed the "Carrier [to adopt] the social forms of their West Coast neighbours." 22 Ultimately, Goldman concluded that "effective social contact between the Alkatcho Carrier, and 20 Goldman, "Crest Prerogatives," 396. 21 Ibid., 417.…”
Section: Introductionmentioning
confidence: 99%